Analysis Of The Effect Of Pitch Value Variation On Image Quality And Examination Time Using A Water Phantom On Head CT Scan Examination Protocol At Ibnu Sina Islamic Hospital Pekanbaru - Nurmajila Nurmajila; Ni Putu Rita Jeniyanthi; I Kadek Sukadana (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: The component that can affect image quality is noise. Noise in CT Scan images comes from random variations in photon detection. Scan time is the time it takes for x-rays to exit for data collection of each slice. Pitch is one of the important component parameters in the CT Scan protocol and fundamentally affects the quality of the resulting image, as well as the time required for scanning. The use of pitch in the Radiology Installation of Ibnu Sina Islamic Hospital Pekanbaru in the head CT Scan examination is 0.55. The pitch value variations used by the author in this study are pitch 0.55, 0.75, 1, 1.25 and 1.5.Methods: This type of research is quantitative research using an experimental approach. The study was conducted to determine the effect of pitch value variation on image quality (noise) and scan time using a water phantom on head CT Scan examination protocol using pitch 0.55, 0.75, 1, 1.25 and 1.5. A sample of 10 CT Scan images was taken, and the image quality (noise) was measured by identifying a specific region in the image (Region of Interest or ROI), while the scan time value was observed from the consul monitor. Data analysis was performed using one-way ANOVA statistical test with a significance level of 5%.Results: The results show that there is a significant difference in image quality (noise) on pitch value variation, with a significance level of 0.004, and there is also a significant difference in scan time on pitch value variations with a significance level of less than 0.001. Conclusions: Based on the conclusion, pitch 1 is the value that produces optimal noise level and scan time in head CT Scan protocol using water phantom.